Optimasi Desain gating system dan riser pada Pengecoran Produk Blok Silinder Modifikasi untuk Motor Bensin 4 Langkah - Bambang Wahyu Sidharta; Nidia Lestari; Venditias Yudha; Eko Wahyudi (Universitas Muhammadiyah Yogyakarta, 2022)
The growth of the automotive industry has made the market demand for motor vehicle spare parts soar, especially motorcycles, including the demand for cylinder blocks. Procedure of this research was carried out to analyze the product of 4 stroke motor cylinder block castings, which include; manufacture of casting product designs, manufacture of gating systems and riser systems. Results and Discussion based on the results of the shrinkage simulation test that has been carried out through the type of sand casting casting with the casting material, namely FCD-600-3 cast iron (1290oC) and the impression material used is silica sand (20oC) with a gravity casting type of casting, it can be concluded that the results of design testing 1 (one) obtained a filling velocity of 1.111 m/s, with a filling time of 3.8 seconds and a required solidification time of 6 minutes. In design 1 (one) there is a shrinkage defect due to shrinkage located on the sprue and riser of 0.336%. While the test results from design 2 (two) obtained a filling velocity of 1.09 m/s, with a filling time of 3.9 seconds and a required solidification time of 5 minutes. In design 2 (two) there is a shrinkage defect due to shrinkage located on the riser and in the cast product of 0.404%. The conclusion of the test results on both designs, it was found that design 1 (one) is the most optimal design for cylinder block casting planning.